Concurrent chemoradiotherapy with/without induction chemotherapy in locoregionally advanced nasopharyngeal carcinoma: Long‐term results of phase 3 randomized controlled trial. Issue 1 (24th January 2019) - Li, Wen‐Fei; Chen, Nian‐Yong; Zhang, Ning; Hu, Guo‐Qing; Xie, Fang‐Yun; Sun, Yan; Chen, Xiao‐Zhong; Li, Jin‐Gao; Zhu, Xiao‐Dong; Hu, Chao‐Su; Xu, Xiang‐Ying; Chen, Yuan‐Yuan; et al.
Abstract : To report long‐term results of a randomized controlled trial that compared cisplatin/fluorouracil/docetaxel (TPF) induction chemotherapy (IC) plus concurrent chemoradiotherapy (CCRT) with CCRT alone in locoregionally advanced nasopharyngeal carcinoma (NPC). Patients with stage III–IVB (except T3–4 N0) NPC were randomly assigned to receive IC plus CCRT (n = 241) or CCRT alone (n = 239). IC included three cycles of docetaxel (60 mg/m 2 d1), cisplatin (60 mg/m 2 d1), and fluorouracil (600 mg/m 2 /d civ d1–5) every 3 weeks. Patients from both groups received intensity‐modulated radiotherapy concurrently with three cycles of 100 mg/m 2 cisplatin every 3 weeks. After a median follow‐up of 71.5 months, the IC plus CCRT group showed significantly better 5‐year failure‐free survival (FFS, 77.4% vs . 66.4%, p = 0.019), overall survival (OS, 85.6% vs . 77.7%, p = 0.042), distant failure‐free survival (88% vs . 79.8%, p = 0.030), and locoregional failure‐free survival (90.7% vs . 83.8%, p = 0.044) compared to the CCRT alone group. Post hoc subgroup analyses revealed that beneficial effects on FFS were primarily observed in patients with N1, stage IVA, pretreatment lactate dehydrogenase ≥170 U/l, or pretreatment plasma Epstein–Barr virus DNA ≥6000 copies/mL. Two nomograms were further developed to predict the potential FFS and OS benefit of TPF IC. The incidence of grade 3 or 4 late toxicities was 8.8% (21/239) in the IC plus CCRT group and 9.2% (22/238) in the CCRT alone group. Long‐term follow‐up confirmed that TPF IC plus CCRT significantly improved survival in locoregionally advanced NPC with no marked increase in late toxicities and could be an option of treatment for these patients. Abstract : What's new? Despite advances in the treatment of nasopharyngeal carcinoma, approximately 30% of high‐risk patients experience recurrence after treatment. Here the authors find that combining the conventional chemoradiotherapy with a triple induction chemotherapy (cisplatin/fluorouracil/docetaxel) prolonged survival of patients with locoregionally advanced cancer, even after more than 70 months of follow‐up. The combination treatment increased acute, but not late, toxicities, and the authors propose that it could present a new treatment option for this patient group.